Relevance of Life Prison in View from the Purpose of Criminal - Rahman, Kholilur; Nainggolan, Samuel Dharma Putra; Sinambela, Jamalum; Budi, Kukuh Pramono; Lestari, Arum Ayu (Universitas Muhammadiyah Surabaya, 2022)
Forms of imprisonment are divided into 2 (two), namely imprisonment for a certain time and imprisonment for life. Life imprisonment is a prison sentence that is served by the convict by remaining in prison until his death. This research is a legal research that uses a statutory approach, and a conceptual approach is used to find out the effectiveness and efficiency of life imprisonment as a form of punishment. This research also describes the ineffectiveness of life imprisonment and seeks to describe forms of punishment that are more appropriate to be carried out in this modern era for the sake of upholding justice and achieving the goals of punishment.